Ta’lîm al-Qâidah al-Arabiyyah an al-Muẓakkar wa al-Mu’annaṡ bi Ṭarîqah al-Lughatain - Latifatul Mahbubah; Moh Wakil (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2022)
Purpose- This study aims to provide information about learning nahwu rules about mudzakkar and muannast in Arabic using the Dual Language Method which combines Arabic and English. Design/Metodology/Approach- This research is a descriptive qualitative research in which the respondents in this study were nahwu teachers and second grade students of TMI Putri Al-Amien Prenduan Sumenep Madura. Findings- The results of this study indicate that learning the nahwu rules about mudzakkar and muannast in Arabic is considered effective for students when taught using the Dual Language Method which combines Arabic and English because all students in this Islamic boarding school use both languages ​​so that it will make it easier for students to learn language rules in both languages. The learning stages are as follows: 1. Introduction, 2. Presentation, connecting and concluding, 3. Practice. Research Limitation/Implications- The limitations of the problem in this research are focused on learning the rules of Mudzakkar and Muannast and have no discussed other nahwu rules. However, this research explains the learning of Musdzakkar and Muannast rules by using the Dual Language Method which involves Arabic and English and is implemented in other nahwu rules. With exercises to ensure students’ understanding so that the learning process can be implemented in other nahwu principles